A MnOOH/nitrogen-doped graphene hybrid nanowires sandwich film for flexible all-solid-state supercapacitors1. Issue 11 (21st March 2015) - Yang, Shuhua; Song, Xuefeng; Zhang, Peng; Gao, Lian
<x xml:space="preserve">Abstract</x> An all-solid-state SC based on a flexible freestanding MNGHNs/AGO electrode with a volumetric capacitance as high as 26.3 F cm−3 is developed.